Utilization of wood ash as seedling media of Cocoa (Theobroma cacao) - Fitria Nugraheni Sukmawati; Zulkifli Zein (University of Darussalam Gontor, Ponorogo, East Java Indonesia, 2016)
An effort to increase productivity is provision of inorganic fertilizers. Inorganic fertilizer application in longtem as found to attenuate the availability of micronutrients and to decrease soil fertility. One possibility to replace inorganic fertilizer is the use of ash derived from plants, such as wood ash. The purpose of this study was to determine the effect of wood ash on soil K availability and to optimize the dose of wood ash which can give good influence on the growth of cocoa seedlings. The experiment was conducted at the experimental station Polytechnic LPP in Wedomartani, Sleman, Yogyakarta. The design used is non factorial randomized block design with 5 treatments, which is the ratio of ash and soil 0: 1 (A1 / Control); 0.25: 1 (A2); 0.5: 1 (A3); 0.75: 1 (A4); and 1: 1 (A5). Observations of treatment effects were made on the seedling height, number of leaves, stem diameter, wet weight and dry weight. Soil analysis was conducted to determine the content of macro elements, micro elements, and pH media. The results showed that ash increases the pH of the media to alkaline range and increase the availability of P and K soil to toxic range. Giving ash reduced the availability of N and caused chlorosis on cocoa seedlings.